2007
DOI: 10.1103/physreve.76.026309
|View full text |Cite
|
Sign up to set email alerts
|

Long-wave Marangoni instability in a binary liquid layer on a thick solid substrate

Abstract: We consider a system which consists of a layer of an incompressible binary liquid with a deformable free surface, and a thick solid substrate subjected to a differential heating across it. We investigate the long-wave thermosolutal Marangoni instability in the case of asymptotically small Lewis and Galileo numbers for finite capillary and Biot numbers with the Soret effect taken into account. We find both long-wave monotonic and oscillatory modes of instability in various parameter domains of Biot and Soret nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…To summarize, we use the minimal model of the surface-tension-driven convection in a layer of binary mixture, disregarding such effects as heat conduction in the substrate (Podolny et al 2007), adsorption-desorption kinetics (Mikishev and Nepomnyashchy 2010, Morozov et al 2013, deformation of the free surface (Podolny et al 2005, 2006, Bestehorn and Borcia 2010, Morozov et al 2013, diffuse interface (Frolovskaya et al 2008), dependence of the Soret coefficient on the concentration (Kalitzova-Kurteva et al 2009, evaporation (Mikishev and Nepomnyashchy 2013) and many others. However, the Soret effect is retained in order to create the gradient of solute concentration and, therefore, to give rise to the unusual mode, which is possible only in a binary liquid (Podolny et al 2005).…”
Section: Governing Equationsmentioning
confidence: 99%
“…To summarize, we use the minimal model of the surface-tension-driven convection in a layer of binary mixture, disregarding such effects as heat conduction in the substrate (Podolny et al 2007), adsorption-desorption kinetics (Mikishev and Nepomnyashchy 2010, Morozov et al 2013, deformation of the free surface (Podolny et al 2005, 2006, Bestehorn and Borcia 2010, Morozov et al 2013, diffuse interface (Frolovskaya et al 2008), dependence of the Soret coefficient on the concentration (Kalitzova-Kurteva et al 2009, evaporation (Mikishev and Nepomnyashchy 2013) and many others. However, the Soret effect is retained in order to create the gradient of solute concentration and, therefore, to give rise to the unusual mode, which is possible only in a binary liquid (Podolny et al 2005).…”
Section: Governing Equationsmentioning
confidence: 99%
“…In particular, due to the Soret effect, temperature differences induce a) Email: eglal.ellaban@ryerson.ca b) Email: jpascal@ryerson.ca c) Email: sdalessio@uwaterloo.ca molecular fluxes leading to non-uniformity in the concentration of the solute. The impact of the Soret effect on the stability of horizontal layers has been extensively studied [9][10][11][12][13][14] . The inclined flow case has received considerably less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, many investigations have been devoted to study the coupled thermal-solutal capillary and buoyancy flows [14][15][16][17]. Results have showed that the thermal-solutal capillary flow and buoyancy flow are coupled in different scales, generating different flow patterns and making diversity of instabilities types [18,19].…”
Section: Introductionmentioning
confidence: 99%